the impact of service quality on customer loyalty in hotel industry - qendah, abd alsalam M.A; , Ihwan Susila, SE., M.Si., Ph.D (2017)
One of the critical success factors that affect the company's performance is service quality. Service quality is the difference between customers expectations for the service encounter and the perceptions of the service received. Customer loyalty is also affecting by service quality. The aims of this study is to analyze the effect of service quality on customer loyalty in the hotel industry. The sampling technique used was purposive sampling. Samples in this study are 150 respondents that are customers Hotel in Surakarta. Based on the results of research and discussion, it can be concluded as follows: assurance has a positive effect on customer loyalty, emphaty has a positive effect on customer loyalty, reliability has a positive effect on customer loyalty, responsiveness has no effect on customer loyalty, tangible has a positive effect on customer loyalty.